Immunolocalization of Prostaglandin E2 Receptor Subtype 4 (EP4) in the Cervix of Cyclic Bitches and Those with Pyometra - P Linharattanaruksa1, K Chatdarong1, S Ponglowhapan1, M Khalid3 and S Srisuwatanasagul2* (Pakistan Veterinary Journal, 2013)
Cervix is an important part of the reproductive tract; in non-pregnant animals it remains closed during anestrus and diestrus and is open only during estrus. In pathological conditions like pyometra, the cervix may be open or closed but the control mechanism is not clearly known. Prostaglandin E2 (PGE2) is considered to be involved in changes of extracellular matrix via coupling to prostaglandin E receptor subtype 4 (EP4). This study investigated the expression of EP4 in the cervices of bitches during different stages of estrous cycle and those with pyometra. After ovariohysterectomy, cervices were collected from anestrus (n=6), estrus (n=12) and diestrus (n=6), open- (n=10) and closed-cervix pyometra (n=10) bitches. Cervical EP4 expression was observed at all the layers and the stages but the differences in EP4 expression either among bitches in different stages of the estrous cycle and between open- and closed-cervix pyometra were limited to only surface epithelium (SE). In cyclic bitches during estrus and in open-cervix pyometra bitches, significantly higher (P<0.05) EP4 expression was found in SE of uterine part than vaginal part. In SE of the uterine part, the expression was higher in the bitches during estrus than in anestrus and diestrus, and in the bitches affected by open-cervix than those with closed-cervix pyometra. The results suggest that regulation of cervical dilation appeared in the uterine part of the cervix. Moreover, EP4 may be involved in stimulating dilation of the cervix in both estrus and open-cervix pyometra bitches.